2001
DOI: 10.3171/jns.2001.95.2.0222
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide reactivity, pressure autoregulation, and metabolic suppression reactivity after head injury: a transcranial Doppler study

Abstract: During the first 2 weeks after moderate or severe head injury, CO2 reactivity remains relatively intact, PA is variably impaired, and metabolic suppression reactivity remains severely impaired. Elevated ICP appears to affect all three components of vasoreactivity that were tested, whereas other clinical factors such as CPP, hypotensive and hypoxic insults, and hemorrhagic brain lesions have distinctly different impacts on the state of vasoreactivity. Incorporation of TCD ultrasonography-derived vasoreactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 63 publications
(77 reference statements)
1
72
0
5
Order By: Relevance
“…Generally, for determination of CO 2 -reactivity methods similar to ours are used [24,25,26], and reactivities are calculated 10 min or 15 min after changing the ventilator settings. Such a time-point may not represent the maximal response in many patients, but rather an arbitrary value that may depend on the rate and extent of induction of hypocapnia.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, for determination of CO 2 -reactivity methods similar to ours are used [24,25,26], and reactivities are calculated 10 min or 15 min after changing the ventilator settings. Such a time-point may not represent the maximal response in many patients, but rather an arbitrary value that may depend on the rate and extent of induction of hypocapnia.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure autoregulation is impaired in most patients after TBI (Lee et al, 2001), and this impairment can persist for up to 2 weeks post-injury (Sviri et al, 2009). In a study with serial measurements of dynamic autoregulation in 122 TBI patients, the lowest ARI value was seen at 48 h post-injury, when 87% of the patients had a value less than the lower limit of normal (Hlatky et al, 2002).…”
Section: Effects Of Hyperventilation and Hyperoxia On Cerebral Pressumentioning
confidence: 99%
“…Clinically, continuous methods of autoregulation tests or monitoring rely on the observation of spontaneous responses of CBF to spontaneous fluctuations in MAP or CPP (Zweifel et al, 2008), arterial partial pressure of CO 2 (Puppo et al, 2008) or metabolites (Lee et al, 2001). Study by Lee in 2001 showed that during the first 2 weeks after head injury, CO 2 reactivity remains relatively intact, pressure autoregulation is variably impaired and metabolic suppression reactivity remains severely impaired and they further noted that unlike hypotension, hypoxia or haemorrhagic brain lesions, elevated ICP appears to affect all components of vasoreactivity that were tested (Lee et al, 2001). In similar year, Czosnyka also noted that autoregulation is not only impaired when associated with a high ICP or low arterial blood pressure, but it can also be disturbed by an excessive CPP (Czosnyka et al, 2001).…”
Section: Two Major Parameters To Consider During Multimodality Monitomentioning
confidence: 99%